Market, value chain and price transmission analyses of the Thai palm oil industry - Songsiengchai, Patchaya (2018)
Drastic movement of global prices for crude oil and palm oil has become a major concern in several countries due to its impact on domestic prices .One of the major concerns is the impact on the price of Thai agricultural products, especially palm oil, because it is the main crop in Thai economic development .Although the country is not a net importer, global price changes of the commodity can transmit to domestic markets for palm oil products. This study aims to examine the structure and marketing system of the palm oil industry in Thailand, also investigates the value chain of the industry as well as analyses price transmission and volatility spillover effect on Thai prices. The study used both primary and secondary data for analyses. For primary data, a survey was conducted in Krabi, a province located in Southern Thailand. For secondary data, this study used prices data for the period of January 1996 to September 2015. Outcomes from the survey were analysed using descriptive and value chain analyses. While the secondary data was analysed using Threshold Cointegration to estimate asymmetric price transmission and Dynamic Conditional Correlation Generalised Autoregressive Conditional Heteroscedasticity (DCC-GARCH) to estimate price volatility effect. In total, the results show that the main players in the Thai palm oil value chain consists of oil palm growers, collection ramps and palm oil mills. The most used trade channel at the farm level is found to be through the ramps, while the direct contact between the growers and millers is minimal. The chain is more likely to be a buyer-driven chain. Trading in the upstream level is based on relational and market coordination, midstream is market coordination, and downstream is industrial coordination. Furthermore, Malaysia crude palm oil and world crude oil prices are found to affect the Thai price. Both positive and negative price shocks bring significant effect to the Thai palm oil price and the price responds faster to the negative shock. Also, high returns in the Thai crude palm oil indicate a positive impact of its uncertainty. Therefore, in order to enhance the Thai palm oil industry and increase global competitiveness, improvements in the relational and market coordination through the grading and harvesting activities at the farm level are needed to ensure higher profit margins for the growers. Besides, the efforts to strengthen the knowledge management aspect on oil palm cultivation and provide financial support may help the growers to improve production and their position in the value chain. Moreover, the government should have effective strategies such as fruits quality control, setting daily price changes ceiling, maintaining a balance domestic stock, and providing the information regarding alternative buyers in the case of excess crude palm oil stock. These strategies will help to improve the capability and efficiency in the production system, thus reducing the risk and fluctuation in Thai palm oil market.